1990
DOI: 10.1093/jnci/82.11.915
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Physical Activity, and Colorectal Cancer Among Chinese in North America and China

Abstract: In a population-based case-control study of colorectal cancer among Chinese men and women in western North America and the People's Republic of China, a common protocol was used to assess past life-style characteristics of 905 cases diagnosed during 1981-1986 and 2,488 controls. Risks for cancers of both the colon and rectum increased with increased food energy from fat, protein, carbohydrate, and all energy sources combined, for both sexes and on both continents. Yet, in multivariate analysis, colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
131
1
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(143 citation statements)
references
References 0 publications
7
131
1
4
Order By: Relevance
“…Most previous studies examining the association between sedentary behavior and physical activity have done so within the context of occupational activity [21,31,37,53]. Le Marchand et al [53] presented evidence that the number of years spent in sedentary or light work only was directly associated with cancer of the proximal colon in both men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies examining the association between sedentary behavior and physical activity have done so within the context of occupational activity [21,31,37,53]. Le Marchand et al [53] presented evidence that the number of years spent in sedentary or light work only was directly associated with cancer of the proximal colon in both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Le Marchand et al [53] presented evidence that the number of years spent in sedentary or light work only was directly associated with cancer of the proximal colon in both men and women. A casecontrol study conducted by Whittemore et al [21] observed that the risk for colon and rectal cancer increased with increasing time spent sitting and for those reporting an overall sedentary lifestyle. To our knowledge, ours is the first large cohort study to document risk of colon cancer associated specifically with time spent in sedentary activities outside of an occupational setting.…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of a food frequency questionnaire, which had been used in previous studies in Shanghai, 14 was utilized to ascertain information on 99 food items. For each item, women were asked ''During most of your adult life how often did you usually eat.…”
Section: Data Collectionmentioning
confidence: 99%
“…10 A prospective cohort study of middleaged Chinese men in Shanghai did not show a significant increase in colorectal cancer mortality among heavy drinkers compared with nondrinkers. 11 Of the 3 case-control studies on colorectal cancer risk in different Chinese populations, 6,7,12 only the 1 by Hu et al 7 from northern China showed the amount of annual alcohol consumption to be an important risk factor for colon cancer and male rectal cancer. Even though there have been numerous studies on the various aspects of alcohol exposure, the effect of drinking cessation on colorectal cancer risk is unknown.…”
mentioning
confidence: 99%